2018
DOI: 10.3390/medicina54020022
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin Complex Concentrate for Warfarin-Associated Intracranial Bleeding in Neurosurgical Patients: A Single-Center Experience

Abstract: Objective: The number of patients presenting with warfarin-associated intracranial bleeding and needing neurosurgical intervention is growing. Prothrombin complex concentrate (PCC) is commonly used for anti-coagulation reversal before emergent surgery. We present our experience with PCC use in patients presenting with coagulopathy and needing urgent craniotomy. Methods: We retrospectively identified all patients presenting with intracranial bleeding and coagulopathy due to warfarin use, requiring urgent neuros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…No difference in mortality and VTE risk Woo, 2014 57 Retrospective chart review 63 VKA-ICH patients FFP vs rFVIIa vs PCC PCC and rFVIIa reached target INR faster than FFP ( p < 0.05). More rebound with FFP and rFVIIa ( p = 0.001) Sarode, 2012 59 Retrospective chart review 46 VKA-ICH patients 3F-PCC and rFVIIa Rapid and effective reversal Astrup, 2018 47 Retrospective chart review 37 patients with urgent reversal Single fixed dose of 1500 IU of 4F-PCC 75% achieved INR ≤ 1.5 100% achieved INR ≤ 2 Mačiukaitienė, 2018 43 Retrospective chart review 35 VKA-ICH requiring urgent neurosurgical procedures 4F-PCC and vitamin K Decrease in INR ( p < 0.01), PT ( p < 0.01), and PTT ( p = 0.02), no adverse effect Scott, 2018 46 Retrospective cohort study 31 VKA-ICH patients 4F-PCC No significant difference between the fixed and weight-based doses of 4F-PCC DOACs studies Pollack, 2017 91 Multicenter, prospective, open-label study 503 patients under dabigatran with bleeding or urgent surgical intervention Idarucizumab 100% of median maximum percentage reversal Siegal, 2015 68 Prospective, randomized, double-blind, placebo-controlled study 101 healthy older volunteers taking Xa inhibitors …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No difference in mortality and VTE risk Woo, 2014 57 Retrospective chart review 63 VKA-ICH patients FFP vs rFVIIa vs PCC PCC and rFVIIa reached target INR faster than FFP ( p < 0.05). More rebound with FFP and rFVIIa ( p = 0.001) Sarode, 2012 59 Retrospective chart review 46 VKA-ICH patients 3F-PCC and rFVIIa Rapid and effective reversal Astrup, 2018 47 Retrospective chart review 37 patients with urgent reversal Single fixed dose of 1500 IU of 4F-PCC 75% achieved INR ≤ 1.5 100% achieved INR ≤ 2 Mačiukaitienė, 2018 43 Retrospective chart review 35 VKA-ICH requiring urgent neurosurgical procedures 4F-PCC and vitamin K Decrease in INR ( p < 0.01), PT ( p < 0.01), and PTT ( p = 0.02), no adverse effect Scott, 2018 46 Retrospective cohort study 31 VKA-ICH patients 4F-PCC No significant difference between the fixed and weight-based doses of 4F-PCC DOACs studies Pollack, 2017 91 Multicenter, prospective, open-label study 503 patients under dabigatran with bleeding or urgent surgical intervention Idarucizumab 100% of median maximum percentage reversal Siegal, 2015 68 Prospective, randomized, double-blind, placebo-controlled study 101 healthy older volunteers taking Xa inhibitors …”
Section: Resultsmentioning
confidence: 99%
“…Prospective, randomized clinical trials show the clinical efficacy of 4-factor PCC in the reversal of warfarin as being superior to that of FFP in patients presenting VKA-related ICH 40 and achieving faster homeostasis in patients needing reversal for surgical interventions. 30 A retrospective observational study demonstrated the efficacy and safety of warfarin reversal using 4-factor PCC and vitamin K in acute ischemic stroke patients before undergoing intravenous thrombolysis; 41 in patients with continuous flow left ventricular assistive devices presenting bleeding or the need for urgent surgery, with no thromboembolic event observed; 42 in patients with intracranial bleeding requiring urgent neurosurgical intervention; 43 and in patients undergoing early orthopedic surgery (within 24 hours) due to hip fractures. 44 In an observational study of 143 patients on warfarin, the use of 4-factor PCC was safe as a reversal agent mainly for bleeding and prior to surgery, with 5 cases of thromboembolic complications.…”
Section: Resultsmentioning
confidence: 99%